The Use of Renewable Energy Within the "Castel Mimi" Tourist Complex - Ciobanu, Victor (Acta Universitatis Danubius. Œconomica, 2025)
The problem addressed is the fight against climate change. The article examines 2 basic aspects: the commitment of the Republic of Moldova to contribute to the reduction of greenhouse gas emissions and the good practices of the “Castel Mimi” Tourist Complex in the use of renewable energy. The objective of the paper is to identify the good practices and motivations that led the owners of the “Castel Mimi” Tourist Complex to switch to alternative energy sources. The paper contains the following question, highlighted as a common thread: how can the objectives of the Paris Agreement on climate change be achieved by involving each economic operator? In order to answer this question, several actions were carried out, including: analysis of strategic materials at the global and local levels, participation in conferences, workshops, which addressed the mentioned subject, visiting the premises of the “Castel Mimi” Tourist Complex and discussions with its administration, interviews, discussions with specialists in the field and with economic operators who implement environmentally friendly practices. The value of the paper lies in presenting arguments for raising awareness among economic operators in the tourism sector of the need to use green technologies in order to ensure the sustainability of their own businesses and to engage in the fight against climate change.